2021
DOI: 10.1088/1742-6596/2094/3/032059
|View full text |Cite
|
Sign up to set email alerts
|

Information system for calculating paper-forming indicators of fibrous semi-finished products based on regression models

Abstract: The paper presents an information system for calculating the main paper-forming parameters of the pulp for given technological and design parameters of the grinding plant. The operation of the system is based on mathematical regression models of the processes that were obtained in the course of experimental studies of knife sets of various types. As input parameters in these models, the rotor speed, knife gap, concentration and degree of grinding of the mass are used. The output parameters are the grinding tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Since in the works of Yu. D. Alashkevich and R. A. Marchenko [6] it was found that knifeless refining has a more gentle, gentle effect on the recycled fiber, which is especially important for a fibrous suspension from waste paper, which has already undergone a refining stage once. Therefore, it can be assumed that the paper-forming properties of the fibrous mass will deteriorate less intensively when recycling using this installation.…”
Section: Methodsmentioning
confidence: 99%
“…Since in the works of Yu. D. Alashkevich and R. A. Marchenko [6] it was found that knifeless refining has a more gentle, gentle effect on the recycled fiber, which is especially important for a fibrous suspension from waste paper, which has already undergone a refining stage once. Therefore, it can be assumed that the paper-forming properties of the fibrous mass will deteriorate less intensively when recycling using this installation.…”
Section: Methodsmentioning
confidence: 99%